Multilingual Children’s Mathematical Engagement with Apps: What Can Be Learned from Multilingual Children’s Mathematical and Playful Participation when Interacting with Two Different Apps? - Fyllingsnes Christiansen, Silje (Conjunctions. Transdisciplinary Journal of Cultural Participation, 2024)
The use of digital tools is becoming increasingly common in early childhood education. One key to using digital tools to enhance learning in children may lie in using them the way children tend to when given the choice: as play. This article examines and evaluates multilingual children’s mathematical engagement with digital apps, focusing specifically on what might be learned from multilingual children’s mathematical and playful participation when interacting with two different apps. Mathematical engagement is here defined by Alan Bishop’s six mathematical activities: counting, measuring, locating, designing, playing and explaining. Helenius et al.’s elaboration of mathematical play is used to connect the mathematical play to the play of children. Multilingual children’s interactions with digital apps have been video recorded in natural settings in a kindergarten. The findings show that playful digital apps do promote the children’s participation in mathematical activities, while apps that aim to provide a formal learning structure seem to promote neither play nor mathematical activities.